2009
DOI: 10.1158/1078-0432.ccr-09-0426
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Zoledronic Acid Impacts Bone Remodeling with Effects on Osteoblastic Lineage and Bone Mechanical Properties

Abstract: Purpose: The increasing incidence of osteonecrosis of the jaw and its possible association with high cumulative doses of bisphosphonate led us to study the effects of high doses of zoledronic acid (ZA) on bone remodeling. Experimental Design: Five-week-old C57BL6 mice were treated with saline or ZA weekly for 3 weeks at increasing doses (0.05-1 mg/Kg). Effects of ZA on bone remodeling were studied using standard assays. Results: We observed an increase in bone mineral density and content in treated animals at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
55
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 50 publications
9
55
0
7
Order By: Relevance
“…Interestingly, the number of empty lacunae in the submucosal bone significantly increased after long-term treatment, suggesting that this finding may be associated with the cumulative doses fixed in the alveolar bone. This fact is in agreement with previous clinical and experimental reports (Ruggiero et al 2009;Marx et al 2005;Allen 2008;Aguirre et al 2012), supporting the hypothesis that long-term exposure to high doses of aminobisphosphonates determines their accumulation in alveolar BMUs, inducing local changes and constituting a potential first step in the development of osteonecrosis of the jaw (Allen 2008;Hoff et al 2008;Daubiné et al 2007;Pozzi et al 2009). …”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Interestingly, the number of empty lacunae in the submucosal bone significantly increased after long-term treatment, suggesting that this finding may be associated with the cumulative doses fixed in the alveolar bone. This fact is in agreement with previous clinical and experimental reports (Ruggiero et al 2009;Marx et al 2005;Allen 2008;Aguirre et al 2012), supporting the hypothesis that long-term exposure to high doses of aminobisphosphonates determines their accumulation in alveolar BMUs, inducing local changes and constituting a potential first step in the development of osteonecrosis of the jaw (Allen 2008;Hoff et al 2008;Daubiné et al 2007;Pozzi et al 2009). …”
Section: Discussionsupporting
confidence: 90%
“…The same study showed that the suppression of bone formation markers was most pronounced in BONJ patients (Raje et al 2008). In addition, a decrease in osteoblasts number was observed in the long bones after 3 weeks of systemic treatment with increasing doses of ZOL (Pozzi et al 2009). Moreover, the absence of woven bone in the alveolar socket after tooth extraction in mice treated with bisphosphonate and denosumab, two agents associated with osteonecrotic-lesions, has recently been demonstrated (Williams et al 2014).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations